Sentidos-e-significados de uma professora alfabetizadora, uma intérprete de libras e uma pesquisadora sobre ensino-aprendizagem de Língua Portuguesa na modalidade escrita - Cassola, Rosangela Vargas (2015)
Considering the importance of the Deaf learning Portuguese as a second language in their socially inclusive process at school, and also anchored in the Theory Socio-Historical-Cultural of Vygotsky (1996, 1997, 2007, 2009, 2010), we aimed to critically understand the process of teaching and learning of Portuguese as a second language for the Deaf. More specifically, we aim to identify and understand the meanings attributed by the regent teacher, the interpreter and the teacher researcher on the Portuguese language teaching and learning in the written form, in an inclusive context. In order to achieve our goal, we decided to develop a critical collaborative research, as this offers important principles for the guidance of studies focus on the transformation of society s attitudes in general. Thus, two types of data were collected. The filming of twelve Portuguese classes attended by the focal student and six reflective study sessions with the regent teacher, interpreter and this researcher. Filming of Portuguese classes occurred in the second year of primary school, in the class of the Deaf student; it is a class in a public school located in a small town in the Midwest of Brazil. After every two classes, we conducted a reflective session, where issues raised by recorded classes were discussed. Data were recorded by audio and video and then transcribed; to establish the linguistic and discourse analysis, we make use of the categories of interaction analysis and types of questions (SMYTH, 1992; SMYTH, 1989; LIBERALI, 2006; 2010; MAGALHÃES, 2011; NININ, 2013). As a result, it was possible to verify the meanings attributed by the regent teacher, the interpreter and researcher on the Portuguese language teaching and learning in the written form, in an inclusive context and also understand that the process of teaching and learning written Portuguese for the Deaf student, mediated by lexicon teaching, does not promote literacy